Correction of Near-infrared High-resolution Spectra for Telluric Absorption at 0.90–1.35 μm. (21st May 2018) - Sameshima, Hiroaki; Matsunaga, Noriyuki; Kobayashi, Naoto; Kawakita, Hideyo; Hamano, Satoshi; Ikeda, Yuji; Kondo, Sohei; Fukue, Kei; Taniguchi, Daisuke; Mizumoto, Misaki; Arai, Akira; Otsubo, Shogo; et al.
Abstract: We report a method of correcting a near-infrared (0.90–1.35 μ m) high-resolution ( λ /Δ λ ∼ 28, 000) spectrum for telluric absorption using the corresponding spectrum of a telluric standard star. The proposed method uses an A0 V star or its analog as a standard star from which on the order of 100 intrinsic stellar lines are carefully removed with the help of a reference synthetic telluric spectrum. We find that this method can also be applied to feature-rich objects having spectra with heavily blended intrinsic stellar and telluric lines and present an application to a G-type giant using this approach. We also develop a new diagnostic method for evaluating the accuracy of telluric correction and use it to demonstrate that our method achieves an accuracy better than 2% for spectral parts for which the atmospheric transmittance is as low as ∼20% if telluric standard stars are observed under the following conditions: (1) the difference in airmass between the target and the standard is ≲ 0.05 ; and (2) that in time is less than 1 hr. In particular, the time variability of water vapor has a large impact on the accuracy of telluric correction and minimizing the difference in time from that of the telluric standard star is important especially in near-infrared high-resolution spectroscopic observation.